Синтезування міфологічних світоглядних основ в українській культурі X-XVI століття - Шарніна, М.В. (Культура народов Причерноморья, 2013)
У статті на матеріалі культури Київської Русі і раннього Відродження розглянуто принцип трансформації світоглядних парадигмальних основ, зокрема, принцип синтезування. Автор робить висновки про те, що у Середньовіччі, головним чином, відбулася міфологізація релігійної свідомості, яка не мислилась тоді і понині без міфу. При цьому релігія, на відміну від міфології, встановлювала трансцендентальний зв’язок людини з Богом через культ. Протягом значного історичного часу відбувалось становлення православних світоглядних принципів за рахунок їхньої адаптації до язичницької парадигми, що і є двовір’ям. В статье на материале культуры Киевской Руси и раннего Возрождения рассмотрен принцип трансформации мировоззренческих парадигмальных основ, в частности, принцип синтезирования. Автор делает выводы о том, что в Средневековье, главным образом, произошла мифологизация религиозного сознания, которая не мыслилась тогда и поныне без мифа. При этом религия, в отличие от мифологии, устанавливала трансцендентальную связь человека с Богом через культ. В течение значительного исторического времени происходило становление православных мировоззренческих принципов за счет их адаптации к языческой парадигме, что и является двоеверие. An active and complex process of globalization which can come into conflict with the revival of national cultures and the formation of the national identity is going on in today’s world. The affirmation of the priority of universal values resulted in the uprising of the interest to the problems of modern development of the Ukrainian culture. The problem of what fundamental ideological positions formed the spirit and spirituality of a pre-historic man and their influence on the formation of a modern man is actual under the conditions of transition to the globalized society. The principle of transformation of the basic paradigmatic world views, in particular, the principle of synthesis is considered in our article on the material relating to the culture of the Kievan Rus and the early Renaissance. The author comes to the conclusion that the Ukrainian culture of the Xth-XV1th centuries which reflects the important principle of synthesis of the mythology-pagan and religious-orthodox paradigm plays an important role in the formation of consciousness and national identity of the Ukrainians. The mytholization of religious consciousness which was naturally impossible without myths themselves took shape in the Middle Ages. The religion unlike the mythology established the transcendental relationship of a man with God through the cult. For a significant historical period the formation of the orthodox world-view principles was going on through their adaptation to the pagan paradigm that appears to be the dual belief.